1997
DOI: 10.1021/ma970337u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stiffness, Monomer Structure, and Energetic Asymmetries on Polymer Blend Miscibilities:  Applications to Polyolefins

Abstract: The generalization of the lattice cluster theory (LCT) to include explicit trans-gauche energy differences is applied to study the combined influences of chain stiffness disparities, monomer molecular structures, energetic asymmetries, and nonrandom mixing on the miscibilities of binary polymer blends. The combination of all these relevant physical features within a single theory enables testing various divergent suggestions concerning the dominant physical factors governing the miscibility of polyolefin blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(103 reference statements)
4
20
0
Order By: Relevance
“…͑PS/ PVME blends are classified as type IV blends, based on fits to blend scattering data and the resulting conditions bϽ0, and a,c 0.͒ Other aspects of non-FH-type critical behavior of PS/PVME blends are described in our prior studies of this system. 8,9,34 Measurements 27,62 and LCT computations 50 for PS/PVME mixtures over a limited range of M indicate a weak M -dependence of the correlation length amplitude o ͑typical values 63 of o are on the order of 10 Å͒, and the theta temperature of PS dispersed at a low concentration in PVME has been estimated 60 as T (PVME) ϭ147°C, a value remarkably close to the critical temperature values found by Han et al, 27 T c ϭ145Ϯ5°C. A similar insensitivity of T c to M is reported 29 for binary blends of PIB with several other polyolefins, which provide additional examples of LCST systems and class IV blends.…”
Section: Experimental Support For New Classes Of Polymer Blend Missupporting
confidence: 70%
See 2 more Smart Citations
“…͑PS/ PVME blends are classified as type IV blends, based on fits to blend scattering data and the resulting conditions bϽ0, and a,c 0.͒ Other aspects of non-FH-type critical behavior of PS/PVME blends are described in our prior studies of this system. 8,9,34 Measurements 27,62 and LCT computations 50 for PS/PVME mixtures over a limited range of M indicate a weak M -dependence of the correlation length amplitude o ͑typical values 63 of o are on the order of 10 Å͒, and the theta temperature of PS dispersed at a low concentration in PVME has been estimated 60 as T (PVME) ϭ147°C, a value remarkably close to the critical temperature values found by Han et al, 27 T c ϭ145Ϯ5°C. A similar insensitivity of T c to M is reported 29 for binary blends of PIB with several other polyolefins, which provide additional examples of LCST systems and class IV blends.…”
Section: Experimental Support For New Classes Of Polymer Blend Missupporting
confidence: 70%
“…The limiting high pressure ͑incompressible͒, high molecular weight LCT can readily be extended to include chain semiflexibility 9 ͑and thereby model chain tacticity͒, but only at the expense of introducing ''bending'' energies E b that reflect the conformational energy differences in the actual polymers. 9 This extension 31 merely renders the two basic counting indices r i and p i as dependent on temperature T, whereupon the a, b, and c in Eqs. ͑8͒ and ͑10͒ then become functions of T. The same Eqs.…”
Section: Of Ref 50͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the recent attempts at refining the Flory-Huggins theory (Bates et al, 1988;Bidkar and Sanchez, 1995;Foreman and Freed, 1997;Schweizer, 1993) lead to a composition-dependent , y parameter that does not vanish in any reasonable limit. It is clear that none of these theories are applicable to the PM/PE system.…”
mentioning
confidence: 99%
“…For example, the synthesis of graft copolymers consisting of poly(ethylene-co-vinyl alcohol) as backbone polymer and PEO as side chains has been performed via anionic polymerization of EO, where the hydroxyl groups of the poly(ethylene-co-vinyl alcohol) backbone were ionized and used as initiation sites for the polymerization of EO. 70 Gohy et al 71 reported the synthesis of amphiphilic PB-gpoly(sodium methacrylate) copolymers via anionic polymerization. Alternatively, anionic polymerization has also been applied in the surface modification of PE with poly(acrylic acid) grafts.…”
Section: Functionalized Polyolefins Via Living Anionic Polymerizationmentioning
confidence: 99%